(untitled) (Homoeopathy for All, 2026)
Dandruff, which in medical terminology is termed as “Pityriasis capitis”, is a common scalp condition characterized by white or grey coloured flakes of dead skin cells from the scalp to appear in the hair. The term Dandruff, being of Anglo Saxon origin, is a combination of two words namely “tan” meaning “vesicular skin disease” and “drof” meaning “dirty”. It generally appears due to constant shedding of the dead skin cells from the scalp in large amounts. When these dead skin cells accumulate either due to inflammation of the scalp or presence of oil in hair, these appear as visible flakes on the scalp, eyelids, shoulders and ears. Other factors such as growth of the fungus called as Malassezia on the scalp that feeds on the natural oil, seborrheic dermatitis, contact dermatitis and underlying skin conditions like psoriasis, eczema which are further aggravated by stress or weather changes, could contribute to this condition.